Long-term outcomes of primary systemic light chain (AL) amyloidosis in patients treated upfront with bortezomib or lenalidomide and the importance of risk adapted strategies - Kastritis, E.; Roussou, M.; Gavriatopoulou, M.; Migkou, M.; Kalapanida, D.; Pamboucas, C.; Kaldara, E.; Ntalianis, A.; Psimenou, E.; Toumanidis, S.T.; Tasidou, A.; Terpos, E.; et al. (American Journal of Hematology, 2015)
Bortezomib and lenalidomide are increasingly used in patients with AL amyloidosis, but long term data on their use as primary therapy in AL amyloidosis are lacking while early mortality remains significant. Thus, we analyzed the long term outcomes of 85 consecutive unselected patients, which received primary therapy with bortezomib or lenalidomide and we prospectively evaluated a risk adapted strategy based on bortezomib/dexamethasone to reduce early mortality. Twenty-six patients received full-dose bortezomib/dexamethasone, 36 patients lenalidomide with oral cyclophosphamide and low-dose dexamethasone and 23 patients received bortezomib/dexamethasone at a dose and schedule adjusted to the risk of early death. On intent to treat, 67% of patients achieved a hematologic response (24% hemCRs) and 34% an organ response; both were more frequent with bortezomib. An early death occurred in 20%: in 36% of those treated with full-dose bortezomib/dexamethasone, in 22% of lenalidomide-treated patients but only in 4.5% of patients treated with risk-adapted bortezomib/dexamethasone. Activity of full vs. adjusted dose bortezomib/dexamethasone was similar; twice weekly vs. weekly administration of bortezomib also had similar activity. After a median follow up of 57 months, median survival is 47 months and is similar for patients treated with bortezomib vs. lenalidomide-based regimens. However, risk adjusted-bortezomib/dexamethasone was associated with improved 1-year survival vs. full-dose bortezomib/dexamethasone or lenalidomide-based therapy (81% vs. 56% vs. 53%, respectively). In conclusion, risk-adapted bortezomib/dexamethasone may reduce early mortality and preserve activity while long term follow up indicates that remissions obtained with lenalidomide or bortezomib may be durable, even without consolidation with alkylators. © 2015 Wiley Periodicals, Inc.